The effect of intravenous Dexamethasone on post-cesarean section pain and vital signs: A double-blind randomized clinical trial - Azar Danesh Shahraki; Awat Feizi; Mitra Jabalameli; Shadi Nouri (Wolters Kluwer Medknow Publications, 2013)
Objective: Any operation leads to body stress and tissue injury that causes pain and its complications. Glucocorticoids such as Dexamethasone are strong anti-inflammatory agents, which can be used for a short time post-operative pain control in various surgeries. Main purpose of this study is to evaluate the effect of administration of intravenous (IV) Dexamethasone on reducing the pain after cesarean. Methods: A double-blind prospective randomized clinical trial was performed on 60 patients candidate for elective caesarean section. Patients were randomly assigned into two groups: A (treatment: 8 mg IV Dexamethasone) and B (control: 2 mL normal saline). In both groups, variables such as mean arterial blood pressure (MAP), heart rate (HR), respiratory rate (RR), pain and vomiting severity (based on visual analog scale) were recorded in different time points during first 24 h after operation. Statistical methods using repeated measure analysis of variances and t-test, Mann-Whitney and Chi-square tests were used for analyzing data. Findings: The results indicated that within-group comparisons including severity of pain, MAP, RR and HR have significant differences (P < 0.001 for all variables) during the study period. Between group comparisons indicated significant differences in terms of pain severity (P < 0.001), MAP (P = 0.048) and HR (P = 0.078; marginally significant), which in case group were lower than the control group. Conclusion: IV Dexamethasone could efficiently reduce post-operative pain severity and the need for analgesic consumption and improve vital signs after cesarean section.